Reliability analysis of safety‐critical and control systems: a state‐of‐the‐art review. Issue 1 (1st February 2018) - Kumar, Vinay; Singh, Lalit; Tripathi, Anil K.
Abstract : In the past several decades, significant attention has been devoted to the quality assessment of safety‐critical (SC) and control systems from many perspectives such as its reliability, safety, and performance. Researchers are continuing to put their efforts to ensure these dependability attributes. This study summarises the state of the art in the field of the reliability of such systems. A detailed literature survey is conducted to investigate the various techniques/models to ensure the reliability of the computer‐based systems. The limitations of these models are also analysed with respect to their applicability in SC systems, for which a case study of nuclear power plant system has been taken. The direction for future research is suggested, based on the case study, to extend the further scope of research.